Using Technologies for Creative- Text Translation - Hadley, James Luke; Taivalkoski-Shilov, Kristiina; Teixeira, Carlos; Toral, Antonio (Taylor & Francis, 2022)
creative texts; translation technologies; machine translation; computer-aided translation; translation practice